2016
DOI: 10.33549/physiolres.933186
|View full text |Cite
|
Sign up to set email alerts
|

Serum Nesfatin-1 Levels in Patients With Different Glucose Tolerance Levels

Abstract: The aim of this study was to compare the levels of nesfatin-1 in healthy subjects with those in prediabetic and diabetic patients who have different glucose tolerance levels. Overall, 100 subjects were divided into 5 groups healthy control (C), impaired fasting glycemia (IFG), impaired glucose tolerance (IGT), metabolic syndrome (MS) and type 2 diabetes mellitus, (Type 2 DM). Glycated hemoglobin (HbA1c) assessed the glycemic control. Homeostasis model assessment of insulin resistance (HOMA-IR) was determined u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 27 publications
7
40
1
1
Order By: Relevance
“…The control group comprised 30 volunteer adults compatible with the case group in terms of age, gender and BMI. The sample size of the study was based on a study examining serum nesfatin-1 levels in individuals with metabolic syndrome 18. Two different samples were calculated in order to make a statistically significant difference of 0.20 units between case and control group.…”
Section: Methodsmentioning
confidence: 99%
“…The control group comprised 30 volunteer adults compatible with the case group in terms of age, gender and BMI. The sample size of the study was based on a study examining serum nesfatin-1 levels in individuals with metabolic syndrome 18. Two different samples were calculated in order to make a statistically significant difference of 0.20 units between case and control group.…”
Section: Methodsmentioning
confidence: 99%
“…However, circulating NUCB2/nesfatin-1 levels were not altered under conditions of type 2 diabetes in rats [ 83 ], whereas in streptozotocin-induced type 2 diabetic mice [ 93 ] and in humans levels were higher in patients with type 2 diabetes or impaired glucose tolerance than in healthy controls [ 100 ], giving rise to species differences. However, in patients with metabolic syndrome, including insulin resistance, NUCB2/nesfatin-1 concentrations were lower than in controls [ 101 ]. A recent meta-analysis failed to show differences in circulating NUCB2/nesfatin-1 concentrations between controls and patients with type 2 diabetes [ 102 ].…”
Section: Implications Of Nesfatin-1 In Blood Glucose Homeostasismentioning
confidence: 99%
“…However, studies evaluating the relationship between circulating nesfatin-1 and type 2 diabetes have produced conflicting results. Some studies revealed high levels of nesfatin-1 in patients with type 2 diabetes [ 8 , 9 ], but others reported lower nesfatin-1 levels in these patients [ 10 – 14 ]. Additionally, the potential causes of these conflicting results have been poorly described.…”
Section: Introductionmentioning
confidence: 99%